2016
DOI: 10.1515/pjvs-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Boar Semen and its Relationship to Sperm Quality Preserved in Commercial Extender Containing Gentamicin Sulfate

Abstract: This study was designed to determine the degree and type of bacterial contamination in boar semen (79 ejaculates from Large White and Landrace boars) and its consequences for sperm quality during storage (27 extended semen samples, 16 o C for five days) under practical conditions of artificial insemination (AI). The results revealed the presence of aerobic bacteria in 99% of the ejaculates (from 80 to 370 ×10 6 colony-forming units/mL). Most of the ejaculates contained two or three bacterial contaminants, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 26 publications
10
54
0
Order By: Relevance
“…However, the current prevalence of bacteriospermia was lower compared to the report of [40], who publicized about 50% in cryopreserved bull semen samples. Moreover, a higher prevalence of bacteriospermia, for instance, 97% [41] and 99% [42] in ram semen and 63% [43] in boar semen, was reported. On the contrary, a lower prevalence comparable to current results, 33.2% [44] and 35.3% [45], was reported in human semen samples.…”
Section: Discussionmentioning
confidence: 95%
“…However, the current prevalence of bacteriospermia was lower compared to the report of [40], who publicized about 50% in cryopreserved bull semen samples. Moreover, a higher prevalence of bacteriospermia, for instance, 97% [41] and 99% [42] in ram semen and 63% [43] in boar semen, was reported. On the contrary, a lower prevalence comparable to current results, 33.2% [44] and 35.3% [45], was reported in human semen samples.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, gentamicin has established itself as one of the most used antimicrobials in boar semen diluents (Schulze et al, 2017). However, Gączarzewicz et al (2016) demonstrated that the inhibitory activity of even gentamicin may be limited during long-term preservation (16°C for five days) in diluent (X-cell ® ). In fact, the storage time is an important factor related to the amount of antimicrobial in the boar semen extender.…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…The number of CFU per mL (CFU mL -1 ) for each sample was calculated by multiplying the average number of colonies counted in duplicates by the inverse of the higher dilution, considering a 100 µL inoculum per plate. C o n s i s t e n t w i t h m e t h o d o l o g y u s e d b y Gaczarzewicz (11), all colonies that grew in Petri dishes containing PCA medium were counted, while only typical total coliform colonies were considered for culture using VRB (1-2 mm in diameter, red with a pinkish precipitation halo).…”
Section: Materiales Y Metodosmentioning
confidence: 99%